Somerset House - Chambers, William
Only at the entrance of the house did a measure of spatial control seem possible within the vast plan of this great building. Here at the Strand Entrances the best of Chamber's work. There were also two great water gates on the south side of the building, but the construction of the Victoria embankment has left these entrances, together with the interior basin, high and dry. As at The Adelphi, this was a building with many levels, but it was never a residence.